Acceptability of policies targeting dietary behaviours and physical activity: a systematic review of tools and outcomes. (29th November 2022) - Scheidmeir, Marie; Kubiak, Thomas; Luszczynska, Aleksandra; Wendt, Janine; Scheller, Daniel A; Meshkovska, Biljana; Müller-Stierlin, Annabel Sandra; Forberger, Sarah; Łobczowska, Karolina; Neumann-Podczaska, Agnieszka; Wieczorowska-Tobis, Katarzyna; Zeeb, Hajo; et al.
Abstract: Background: Successful implementation of health policies require acceptance from the public and policy-makers. This review aimed to identify tools used to assess the acceptability of policies targeting physical activity and dietary behaviour, and examine if acceptability differs depending on characteristics of the policy and of the respondents. Methods: A systematic review (PROSPERO: CRD42021232326) was conducted using three databases (Science Direct, PubMed and Web of Science). Results: Of the initial 7780 hits, we included 48 eligible studies ( n = 32 on dietary behaviour, n = 11 on physical activity and n = 5 on both), using qualitative and quantitative designs ( n = 25 cross-sectional, quantitative; n = 15 qualitative; n = 5 randomized controlled trials; n = 3 mixed-methods design). Acceptability was analysed through online surveys ( n = 24), interviews ( n = 10), focus groups ( n = 10), retrospective textual analysis ( n = 3) and a taste-test experiment ( n = 1). Notably, only 3 (out of 48) studies applied a theoretical foundation for their assessment. Less intrusive policies such as food labels and policies in a later stage of the implementation process received higher levels of acceptability. Women, older participants and respondents who rated policies as appropriate and effective showed the highest levels of acceptability. Conclusion: Highly intrusive policies such as taxations or restrictions are the least accepted when first implemented, but respondents' confidence in the relevance and effectiveness of the policy may boost acceptability over the course of implementation. Studies using validated tools and a theoretical foundation are needed to further examine opportunities to increase acceptability.